Fiscal monitoring policy and corporate social responsibility - Ahmed, Mohamed Shaker; Ali, Searat; Mertzanis, Charilaos; King, Timothy (Elsevier, 2026)
This paper examines how state-level fiscal monitoring policy (FMP) affects firms' corporate social responsibility (CSR) performance. Using a sample of S&P 500 firms from 2001 to 2020 and exploiting staggered FMP adoption across U.S. states, we employ a difference-in-differences framework and document a positive, statistically significant relationship between FMP adoption and firms' CSR. Economically, FMP adoption is associated with an approximately 2.64% increase in CSR performance. We can interpret this result as fiscal monitoring reducing local corruption and strengthening institutional governance by enhancing fiscal transparency, enforcement credibility, and long-term orientation. While CSR is the outcome of interest, our findings provide new evidence on the private-sector spillover effects of fiscal monitoring policy, extending the FMP literature beyond public-sector outcomes. Additional analyses show that environmental dynamism, product-market competition, financial constraints, and geographic dispersion weaken the FMP–CSR relationship, whereas right-to-work laws strengthen it. Overall, our study highlights subnational fiscal governance as a novel institutional determinant of corporate behavior.
Keywords: Fiscal monitoring; Corporate social responsibility; ESG; Governance; Stakeholder theory; Corruption; Institutional governance; fi=Rahoitus|en=Finance|